"The Persistence of Parent Repayment" and the Anticipation of Filial Obligations of Care in Two Thai Provinces. Issue 2 (21st February 2014) - Basten, Stuart; Muttarak, Raya; Pothisiri, Wiraporn
<x xml:space="preserve">Abstract</x> With an accelerated and sustained decline in fertility and an increase in life expectancy, Thailand has entered its aging phase at a rapid pace. This raises an important question of who should care for the increasing elderly population. Using a survey of adults aged 16–64 years (n = 742) in two provinces in the north‐east (Kalasin) and south (Phang Nga) of Thailand, this paper explores the expectations that individuals have from their children when they become very old. Only one‐third of the respondents expected to live with their children in old age and only one‐fifth anticipated financial assistance. Less than half of them expected personal care and practical care from their children (43% and 38%, respectively). The expectations varied substantially by the number of children and income, with those with higher income reporting lower expectation. Those living in Kalasin, a much poorer province than Phang Nga, had greater expectations from their children in old age. This suggests that, for those with less financial resources, children remain the main care provider for the elderly.